A reception study of media marketing motorcycles - Tiong, Michael Hock Bing (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The purpose of the dissertation is to examine the process of consumers „reading‟ the media advertising of motorcycles. This is an interpretive study to understand the perception prior to consumption, or consumption of advertising. Consumers‟ understanding and sense making of media advertising as well as their reaction towards the interpreted media advertising were studied. In detail, an Interpretive phenomenology study was conducted of the cognitive responses of twenty four postgraduates at a higher learning institution in Sarawak, so as to explore rather than explain the experience of meaning construction when viewing the motorcycle videos. The narratives of the participants‟ understanding process were audio recorded, transcribed and analysed. The results identified seven stages of participants interpreting the motorcycle videos – absorption, anticipation, articulation, alignment, appropriation, alienation, and analysis. These „moments‟ or stages can be supported as a process of understanding by referring to phenomenology. Participants of the study authorised accounts of the narrative‟s content by using their own cultural knowledge, aligning with or being alienated by their perceptions of the bike branding narratives, further building the brand. The dissertation is of practical value to the advertisers and marketers who plan to develop media advertising of motorcycles as it provides research on consumers‟ needs and preference for the type of media advertising and hence can be taken up when planning such advertisements in order to design advertisements with features that are most salient to the audience who are always actively interpreting the narratives while reading them. The results iii from this dissertation will also add to the empirical database on interpretive marketing research in Malaysia.